1991
DOI: 10.1091/mbc.2.10.819
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of calmodulin gene expression in rat brain and skeletal muscle.

Abstract: Three different calmodulin genes that encode the identical protein have been identified in the rat (Nojima, 1989); however, calmodulin gene expression at the various stages of tissue differentiation and maturation has not been previously determined. We have quantitated the content of mRNAs encoding calmodulin in the developing brain and skeletal muscle using RNA blot analysis with three specific cDNA probes. Our results show that five species of calmodulin mRNAs: 4.0 and 1.7 kb for CaM I, 1.4 kb for CaM II, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…They are strongly expressed in neural tissue (Nojima 1989;Weinman et al 1991;Ikeshima et al 1993). Under physiological conditions, a similar expression pattern in the rat brain Gannon and McEwen 1994) but a differential expression in the mouse brain (Solà et al 1996) have been reported for the three CaM genes.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…They are strongly expressed in neural tissue (Nojima 1989;Weinman et al 1991;Ikeshima et al 1993). Under physiological conditions, a similar expression pattern in the rat brain Gannon and McEwen 1994) but a differential expression in the mouse brain (Solà et al 1996) have been reported for the three CaM genes.…”
supporting
confidence: 54%
“…The CaM genes exhibit tissue-specific expression with differential regulation during development in the rat (McManus et al 1989;Weinman et al 1991;Ikeshima et al 1993). They are strongly expressed in neural tissue (Nojima 1989;Weinman et al 1991;Ikeshima et al 1993).…”
mentioning
confidence: 99%
“…These data indicate that in lymphocytes only CALM3 is linked to the proliferation state of the cells. This finding is in contrast to the fact that in many other cell lines and rat tissues CALM2 mRNA was the most highly expressed (MacManus et al, 1989;Slaughter and Means, 1989;Bai and Weiss, 1991;Dowd et al, 1991;Weinman et al, 1991;Christenson and Means, 1993) and considered to be the gene associated with proliferation (Chafouleas et al, 1984b;Sommer et al, 1989;Christenson and Means, 1993). CALM2 has been also proposed to play the major role in determining the changes in cellular CaM protein levels (Christenson and Means, 1993).…”
Section: Discussionmentioning
confidence: 89%
“…However, a differential regulation of the three genes has been observed in several developmental systems (MacManus et al, 1989;Slaughter and Means, 1989;Weinman et al, 1991), whereas in several other cases a coordinate upregulation (Bai and Weiss, 1991;Dowd et al, 1991;Colomer et a1.,1993) or down-regulation (Christenson and Means, 1993) CALM transcripts has been shown in the late GI-S phase during proliferative activation of several cellular types (Chafouleas et al, 1984b;Colomer et al, 1993). The elevation of CALM mRNAs led to the increase of total CaM protein (Chafouleas et al, 1984b;Bai and Weiss, 1991;Dowd et al, 1991;Christenson and Means, 1993;Colomer et al, 1993).…”
mentioning
confidence: 99%
“…Although the reason for the presence of multiple synonymous genes in animals is unclear, differences in the 5' and 3' non-coding region of the rat CaM genes suggest that each gene may be differentially regulated. The overall distribution of the three CaM transcripts was coordinated in rat brain , however, temporal and spatial differences in the expression of CaM genes have been observed in some areas of the CNS, both under physiological and experimental conditions (Michelhaugh et al, 1998;Palfi et al, 2000, Palfi et al, 2001, Shimizu et al, 1997Sola et al, 1997;Weinman et al, 1991). Knowledge of the evolutionary relationships between vertebrate CaM genes should provide useful information (in) regarding (to) this multiple-gene system.…”
Section: Introductionmentioning
confidence: 99%